PLOT GENERATOR AS DIGITAL TOOL IN ASSISTING THE TEACHER IN WRITING ACTIVITY - Irma Yanti; Amaluddin Amaluddin; Siti Hajar (Universitas Muhammadiyah Makassar, 2021)
This research aims to know how Plot Generator in assisting the teacher in a writing activity.This research used survey research design with quantitative method. Three English teachers participated as subjects of the research in senior high education in BARRU. The steps of collecting data were conducted by observation and questionnaire, The observation was conducted by distributed questionnaires to guide data as prior knowledge before conducting research. Questionnaire as the instrument of the research to gain the information related plot generator in assisting teacher in writing activity. The data were analyzed by using Likert Scale that presented by quantitative data. The results of this study indicate that Plot Generator assists the teacher in a writing activity by assist of function, source and content that is presented by teachers’ perception toward Plot Generator.